2018
DOI: 10.1002/pi.5687
|View full text |Cite
|
Sign up to set email alerts
|

Physicochemical properties of reduced graphite oxide conglomerated polyethylene nanocomposites

Abstract: The variation in physicochemical properties on incorporation of unmodified reduced graphite oxide (rGO) into a low‐density polyethylene (LDPE) matrix has received much attention. Herein, a simple method is developed for the fabrication of LDPE/rGO nanocomposites using a solvent casting method. The UV‐visible spectra showed that addition of rGO can effectively cut off the short‐wavelength UV‐B light, which resists the occurrence of photoreaction. The stiffness of the LDPE/rGO nanocomposites was improved by 45% … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 62 publications
0
5
0
Order By: Relevance
“…Similar to other polymer matrices, the combination of graphene with polyolefins generally leads to mechanically stronger nanocomposites with improved thermal stability [ 10 , 11 , 12 , 13 , 14 , 15 , 16 ]. The former is attributed to a barrier effect of the nanomaterial that effectively hinders the transport of volatile decomposition products from the bulk of the polymer to the gas phase, hence retarding the degradation process [ 13 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Similar to other polymer matrices, the combination of graphene with polyolefins generally leads to mechanically stronger nanocomposites with improved thermal stability [ 10 , 11 , 12 , 13 , 14 , 15 , 16 ]. The former is attributed to a barrier effect of the nanomaterial that effectively hinders the transport of volatile decomposition products from the bulk of the polymer to the gas phase, hence retarding the degradation process [ 13 ].…”
Section: Introductionmentioning
confidence: 99%
“…Beyond electrical conductivity, gas barrier is also one of the most explored functionalities for this kind of materials [ 28 ] due to the important role that polyethylene plays in packaging for food and pharma applications. In order to solve the problem of high permeability to gases, the incorporation of laminar nanoparticles such as graphene has been intensely investigated [ 10 , 11 , 12 , 14 , 15 , 16 , 29 , 30 , 31 , 32 ]. Graphene nanosheets are intrinsically impermeable to almost all gas molecules [ 33 ] and also present high aspect ratio structures, which make them ideal to engineer tortuous pathways to decrease the molecular diffusion rates through polymeric materials [ 34 , 35 ].…”
Section: Introductionmentioning
confidence: 99%
“…The PNC showed a 26% improvement in the oxygen barrier property with the addition of 0.3 wt% rGO, where a further increase in the amount of rGO from 0.3 wt% did not lead to any significant changes in the oxygen permeability. Furthermore, an improvement of 45% in the stiffness was also reported for the PNC [ 101 ]. Kim et al coated an EVOH/graphene oxide composite on the surface of a biaxially oriented (BO) PP film.…”
Section: Barrier Properties Of Polymer Nanocompositesmentioning
confidence: 67%
“…Toh et al reported on a reduced graphene oxide (rGO)/PE nanocomposite [ 101 ]. The PNC showed a 26% improvement in the oxygen barrier property with the addition of 0.3 wt% rGO, where a further increase in the amount of rGO from 0.3 wt% did not lead to any significant changes in the oxygen permeability.…”
Section: Barrier Properties Of Polymer Nanocompositesmentioning
confidence: 99%
“…Like other polymer matrices, graphene and polyolefins together typically produce physically stronger nanocomposites with increased heat stability, [10][11][12][13][14][15][16]. The former is ascribed to the barrier effect of the nanomaterial, which successfully prevents the passage of volatile breakdown products from the bulk of the polymer to the gas phase, delaying the degradation process, [13].…”
Section: Introductionmentioning
confidence: 99%